Sosial Media Marketing untuk Meningkatkan Kunjungan Wisatawan: Studi Kasus pada Desa Wisata Pentingsari Yogyakarta - Ariyanti, Siska; Arviania, Nerissa; Zaki, Ahmad (Sosio e-Kons, 2025)
Digital marketing is an activity of managing and implementing marketing using electronic media such as websites, emails, and other mobile media that aims to achieve marketing goals through the application of digital technology. Pentingsari Tourism Village is a village located in Umbulharjo Village, Cangkringan District, Sleman Regency, Special Region of Yogyakarta. The tourist village has natural beauty, agro-tourism, and cultural appearances that have the potential to be tourist attractions. In an effort to build branding and expand marketing, the Pentingsari tourism village has utilized digital media. This research aims to find out the use of digital marketing as a marketing effort in Pentingsari tourism villages. The research method used is a qualitative method with descriptive analysis. Data collection is carried out through library research and documentation. The research data was analyzed in a qualitative descriptive manner. The results of the study show that the marketing of the Pentingsari tourism village is carried out through the website, Instagram, Tiktok, Facebook, Youtube, Live Inn Video, and the Google Map application. The use of digital marketing aims to expand market reach and increase tourist visits to the Pentingsari tourist village. In its implementation, the use of digital marketing has not been managed optimally due to limited human resource capabilities. This requires training to improve the capabilities of human resources. The conclusion of this study is that digital marketing is one of the efforts to expand the marketing of the Pentingsari tourist village, Sleman Regency so that it can increase the interest in visiting tourists.